Analisis Penerapan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) di PT YZ - Pratama, Naufal Adetresna; Herwanto, Dene (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This study aims to analyze the implementation of the Hazard Identification Risk Assessment and Risk Control (HIRARC) method at PT. YZ, a manufacturing company engaged in cartons and packaging. The HIRARC method consists of three main steps: hazard identification, risk assessment, and risk control. The implementation of this method aims to minimize potential workplace accidents and ensure worker safety. The research was conducted through direct observation, interviews, and data collection in the warehouse. The identification results revealed several potential hazards, such as slipping, inhaling dust, chemical exposure, and unsafe storage practices. Based on risk matrix analysis, it was found that the extreme risk was inhaling dust, while the high risk was chemical exposure. Risk control measures were implemented through the use of personal protective equipment (PPE) such as helmets, masks, and safety shoes, as well as ventilation improvement, safety training, and rearrangement of storage systems. In conclusion, the application of the HIRARC method provides a systematic approach to improving workplace safety at PT. YZ. Recommendations for the company include enhancing safety training and implementing routine inspections to ensure a safer working environment. Keywords: HIRARC, Hazard Identification, Occupational Safety, Risk Assesssment